Study on the moisture adsorption isotherms and different forms of water for lignite after hydrothermal and thermal upgrading. (15th June 2019) - Zhang, Xiaopei; Zhang, Cheng; Feng, Xiaofei; Yu, Shenghui; Li, Xin; Fang, Qingyan; Chen, Gang
Abstract: Lignite has a high moisture content and needs to be dewatered before use. However, dewatered lignite will readily reabsorb moisture due to its unique physicochemical structure. In this work, a typical Chinese lignite was hydrothermally upgraded at 150–300 °C and thermally upgraded at 200–500 °C before analysing its moisture readsorption properties. The modified Brunauer, Emmett and Teller (BET) model was applied to analyse the moisture adsorption isotherms of lignite. Different forms of water were determined by thermogravimetry coupled with differential scanning calorimetry (TGA-DSC). With increasing upgrading temperature, the primary and secondary adsorption contents of lignite decreased constantly for both hydrothermal and thermal upgrading. At the same upgrading temperature, hydrothermal upgrading was more effective in lowering the primary and secondary adsorption contents. Three forms of water were distinguished in lignite. The sequence of desorption heat was molecular water > capillary water > free water, while the sequence of water content was free water > molecular water > capillary water. With increasing upgrading temperature, the free water content first increased slightly and then decreased significantly, while the capillary water content and molecular water content decreased continuously. Hydrothermal upgrading was more effective than thermal upgrading in inhibiting the moisture readsorption of lignite.